Externalized transapical guidewire technique after artificial aortic valve replacement during complete endovascular aortic arch repair - Tomasz Jędrzejczak (Termedia Publishing House, 2020)
An externalized transapical guidewire (ETAG) technique has been used for safe delivery of high-profile devices through a tortuous aorta to zone 0, which is currently precluded after mechanical artificial aortic valve replacement (AVR). The aim of the study was to report one center’s experience (based on 3 cases) of a unique modification to the ETAG technique used for the first time during total endovascular aortic arch repair after AVR. This report contains technical notes regarding a new method of steering the guidewire from the apex inside the artificial aortic valve during total endovascular aortic arch repair after AVR and the details crucial in preparation for this mini-invasive procedure. As a conclusion, the ETAG technique could be performed after mechanical AVR with active positioning of the guidewire carried out under the control of transesophageal echocardiography.